Hubungan Eating Behavior dan Sedentary Lifestyle dengan Status Gizi Lebih pada Remaja Fase Awal - Silvi Saffanatul Hasanah (Media Gizi Kesmas, 2024)
Background: Overweight is a serious public health problem than can negatively impact quality of life. Overweight adolescents at risk of weight problems as adults. Eating behavior and sedentary lifestyle are closely related to overweight in adolescents because they can affect the energy balance in the body. Objectives: This study aims to analyze the relationship of eating behavior and sedentary lifestyle with overweight status in early adolescents. Methods: This study used a cross sectional design with a sample size of 85 students of MTsN 5 Nganjuk. Sampling using stratified random sampling method. Data were collected directly, including data on respondent characteristics, filling out the Dutch Eating Behavior Questionnaire, Adolescent Sedentary Activity Questionnaire, and anthropometric measurements. Data analysis was performed using the Spearman Correlation test. Results: The majority of the respondents (56.5%) were female and in the 13–15 age group. Due to a family history of obesity, 65.9% of respondents overall had a hereditary predisposition to being overweight. The majority of respondent's eating patterns (82.4%) were external. The majority of respondents (82.4%) engaged in a lot of sedentary activities. 34.1% of respondents overall reported being overweight. The result showed that there was no significant relationship between emotional eating (p-value=0.213) and external eating (0.508) with overweight. There was a significant relationship between restraint eating (p-value=0.030) and sedentary lifestyle (p-value=0.047) with overweight. Conclusions: Early teenage overweight status has no association with external eating behavior or emotional eating. Restricted eating habits and a sedentary lifestyle are significantly correlated with early-stage teenage overweight status. To enhance health status in the early teenage age group, it is important to increase awareness of the prevalence of overnutrition, regulate food intake by upholding healthy eating habits, and lower the level of sedentary lifestyle.